Adiponectin, AFABP, and leptin in human breast milk during 12 months of lactation - Bronsky, Jiri; Mitrova, Katarina; Karpisek, Michal; Mazoch, Jiri; Durilova, Marianna; Fisarkova, Barbora; Stechova, Katerina; Prusa, Richard; Nevoral, Jiri (Journal of pediatric gastroenterology and nutrition, 2011)
OBJECTIVES: Adiponectin, adipocyte fatty acid-binding protein (AFABP), and leptin have been shown to be present in human breast milk (BM). We determined intraindividual changes of BM levels of these proteins during 12 months of lactation. SUBJECTS AND METHODS: Proteins were measured using a high-sensitivity enzyme-linked immunosorbent assay method in 72 healthy mothers after delivery (day 0, D0) and after 1, 3, 6, and 12 months of lactation. RESULTS: Adiponectin levels in BM on D0 were 22.8 ± 0.8 (mean ± standard error of the mean), in 1 month (M1) 22.0 ± 0.6, in 3 months (M3) 20.5 ± 0.6, in 6 months (M6) 21.4 ± 0.8, and in 12 months (M12) 25.7 ± 1.4 ng/mL. AFABP levels were 12.3 ± 2.0, 6.2 ± 1.3, 1.3 ± 0.2, 2.5 ± 1.0, and 4.6 ± 1.9 ng/mL, respectively. Leptin levels were 0.3 ± 0.04, 0.2 ± 0.03, 0.1 ± 0.01, 0.1 ± 0.02, and 0.2 ± 0.04 ng/mL, respectively. We found significantly higher levels of adiponectin in M12 in comparison to M3 and M6 (P = 0.0026), higher levels of AFABP in D0 and M1 when compared with M3, M6, and M12 (P < 0.0001), and higher levels of leptin on D0 than in M1, M3, M6, and M12 (P < 0.0001). AFABP levels correlated negatively with infants' body weight in M1, but there was no correlation throughout the lactation period between body weight and other proteins. We found positive correlation between adiponectin, AFABP, and leptin throughout the lactation. CONCLUSIONS: All of the hormones were detectable in BM up to 12 months of lactation, with decreasing trend until M3 and subsequent increase till M12. We speculate that higher levels in M6 and M12 may be caused by longer intervals between breast-feeding due to the introduction of complementary food.
Keywords: Fatty Acid-Binding Proteins; novorozenec; Infant, Newborn; proteiny vázající mastné kyseliny; Infant; Humans; Pregnancy; kojenec; porodní hmotnost; mateřské mléko; Female; dospělí; Colostrum; lidé; reprodukovatelnost výsledků; časové faktory; Adult; vývoj dítěte; kolostrum; ženské pohlaví; Milk, Human; laktace; Male; Leptin; Child Development; Adiponectin; Birth Weight; Reproducibility of Results; leptin; těhotenství; Czech Republic; adiponektin; Body Weight; tělesná hmotnost; mužské pohlaví; Česká republika; Lactation; Time Factors